Design and Construction of Mice Detection and Removal Equipment in the House Based on the Internet of Things (IoT) - Lubis, Zakia; Nasution, Mulkan Iskandar; Nasution, Nazaruddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Rats are rodents that have a negative impact on society, both in agriculture and industry. Rodents roaming around in the house can damage electrical connections, which can trigger fires and cause fires, as well as causing economic losses. This research used a PIR sensor to detect movement and an ESP32 cam to stream live video on the blynk application. Box two contains a series of ultrasonic sound generators emitted through speakers. Additionally, tool tests were carried out using a 12 V battery test, PIR sensor test, relay test, ESP32 Cam, ultrasonic generator PWM test, Blynk test, and tool test on mice. This research aims to design a device for detecting and repelling mice in homes based on the Internet of Things (IoT). The design of this tool uses an ESP32 microcontroller as the main controller. This tool also has components such as an ESP32 cam, relay, ultrasonic speaker, 3.7-volt battery, PIR sensor, servo motor, and ultrasonic sound generator module. This tool has a working system in the form of a PIR sensor that detects mouse movement. Then the ultrasonic sound automatically comes on, the servo motor moves and the ESP32 cam connected to the Blynk application will stream live video. This tool also has an on and off button system via the blynk application. The test results carried out by the PIR sensor were able to detect the presence of objects at a distance of 5 m. The frequency issued by the ultrasonic module and measurements made via an oscilloscope has an average percent error of 1,02%. This proves that the performance of the designed prototype tool works well. The results of tests to repel mice using ultrasonic sound, which could disturb the mice, were at 40-50 kHz. The overall test results for the home IoT-based mouse detection and repellent system worked well.